Content Analysis of the Digital Skills Course for the Primary Stage in Kingdom of Saudi Arabia in Light of The Digital Citizenship Values - Alshuhaywin, Nouf Majed Saad; Alshehri, Ajlan Mohammed Houjeer (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the degree of inclusion of digital citizenship values in the digital skills course for the upper primary stage in the second semester 1443 AH. In order to achieve the objective of the study and answer its questions, the analytical descriptive approach was employed, as well as content analysis approach. The research tool was the content analysis card, which was formed in light of the values of digital citizenship, which are nine criteria: digital security, digital commerce, digital access, digital communications, digital security and safety, digital laws, digital literacy, digital rights and responsibilities, digital health. The study reached several results, the most important of which is that the course is characterized by smoothness and clarity in presentation, and the appropriate size of the knowledge content. The degree of inclusion of digital citizenship values in the digital skills course is very low to low, ranging from (zer%) to (21.3%), the values of digital citizenship that should be available in the digital skills course for the upper primary stage in the second semester of the year 1443 AH, are represented by (78) indicators. The study recommended a number of recommendations, the most important of which is the continuation of the development of educational curricula and their inclusion of digital citizenship standards, educating male and female teachers at all stages of the importance of digital citizenship standards, and designing a curriculum for digital skills for all educational stages, promote cooperation "Ministry of Educational" and "Ministry of Communication and Information Technology".
Keywords: Courses and Curricula; Digital skills; Digital Citizenship